The Influence of Customer Ratings and Reviews on Online Electronic Product Purchase Decisions - Asep Nugraha; Dicky Fauzi Firdaus (Politeknik Siber Cerdika Internasional, 2025)
The rapid growth of e-commerce has created information asymmetry challenges, as consumers cannot physically inspect products before purchasing. Customer ratings and reviews, as forms of electronic word-of-mouth (eWOM), have emerged as critical information sources, yet their specific influence on Indonesian consumers remains underexplored. This study aims to analyze the influence of customer ratings and reviews on online purchase decisions for electronic products in Indonesia's e-commerce platforms. Using a quantitative approach, data were collected from 280 respondents through an online survey with Likert scale questionnaires. Data analysis utilized multiple linear regression with SPSS 25.0, including validity and reliability tests (Cronbach's Alpha), classical assumption tests (Kolmogorov-Smirnov, VIF, Tolerance, Glejser, linearity), partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination (R²).The results indicate that customer ratings significantly influence purchase decisions (t = 5.847, p < 0.05), customer reviews have an even stronger influence (t = 8.329, p < 0.05), and both variables simultaneously show significant influence (F = 64.238, p < 0.05) with R² = 0.315. These findings confirm that eWOM serves as a critical component in Indonesian consumers' decision-making process for purchasing electronic products online, with important implications for e-commerce platforms and digital marketing strategies.